PENGEMBANGAN MEDIA PEMBELAJARAN MATERI BOLA VOLI BERBASIS ANDROID MENGGUNAKAN SOFTWARE I SPRING SUITE : Enhancing Physical Education through Interactive Digital Media - Dandy Novantua Nababan; Rama Kurniawan; Hertika Yusniawati (Fakultas Ilmu Keolahragaan Unimed, 2026)
The purpose of this study is to develop valid, practical, and effective physical education learning media. The volleyball learning media developed in this study is a physical education learning media with the topic of volleyball. The research and development model uses the ADDIE model procedure. This product trial determines the level of feasibility of the product developed. Data collection uses observation and interviews for needs analysis and questionnaires for data from evaluations of learning experts, media experts, practitioner experts, small group and large group trials, and assessments of students of SMPN 3 Malang. The data analysis technique uses quantitative descriptive statistical analysis. Based on the results of the learning expert analysis with an average of 99%, then the results of media experts averaged 100%, while the results of material experts averaged 98%. In small group trials, the percentage was 84%, for the results of data in large group trials, the percentage was 90%. It is concluded that the application-based volleyball material teaching media can be stated to have very valid clarity, ease, attractiveness, suitability and accuracy and this application product is worthy of use in learning activities.